2005
DOI: 10.1093/hmg/ddi306
|View full text |Cite
|
Sign up to set email alerts
|

Novel glycogen synthase kinase 3 and ubiquitination pathways in progressive myoclonus epilepsy

Abstract: Lafora progressive myoclonus epilepsy, caused by defective laforin or malin, insidiously present in normal teenagers with cognitive decline, followed by rapidly intractable epilepsy, dementia and death. Pathology reveals neurodegeneration with neurofibrillary tangle formation and Lafora bodies (LBs). LBs are deposits of starch-like polyglucosans, insufficiently branched and hence insoluble glycogen molecules resulting from glycogen synthase (GS) overactivity relative to glycogen branching enzyme activity. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
152
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(163 citation statements)
references
References 45 publications
8
152
0
3
Order By: Relevance
“…The measurements of bulk enzyme activity, though, do not give much mechanistic insight into the cause of Lafora body formation. The increased glycogen synthase protein would be consistent with the proposal that laforin participates in glycogen synthase degradation but not that it activates GSK-3 by NH 2 -terminal dephosphorylation [23]. Branching enzyme activity is also increased in the transgenic muscle so that the ratio of glycogen synthase to branching activities is little changed.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The measurements of bulk enzyme activity, though, do not give much mechanistic insight into the cause of Lafora body formation. The increased glycogen synthase protein would be consistent with the proposal that laforin participates in glycogen synthase degradation but not that it activates GSK-3 by NH 2 -terminal dephosphorylation [23]. Branching enzyme activity is also increased in the transgenic muscle so that the ratio of glycogen synthase to branching activities is little changed.…”
Section: Resultssupporting
confidence: 85%
“…Loss of function mutations in EPM2B should thus stabilize laforin making it hard to understand how recessive mutations in either EPM2A or EPM2B result in the disease. Lohi et al [23] found that malin interacts also with glycogen synthase and propose that the laforin-malin-glycogen synthase complex is targeted for degradation. In the same study, it was also reported that laforin could dephosphorylate the NH 2 -terminal inhibitory phosphorylation site of the protein kinase GSK-3 which should result in glycogen synthase inactivation.…”
mentioning
confidence: 99%
“…4). While the mutation did not affect the subcellular localization of the laforin mutant, the phosphatase activity of the pro- (Gentry et al 2005), and glycogen synthase kinase 3 (GSK3) (Lohi et al 2005a). Laforin-laforin interaction has also been documented (Fernandez-Sanchez et al 2003).…”
Section: Epm2amentioning
confidence: 97%
“…Malin interacts at least with four distinct E2 ubiquitin conjugating enzymes (Ubc) involved in the ubiquitination process: UbcH2, UbcH5a, UbcH5c and UbcH6 (Gentry et al 2005). GS is regulated by GSK3, and the activity of GSK3 is shown to be modulated by laforin (Lohi et al 2005a). Laforin and malin, therefore, appear to regulate critical steps in glycogen metabolism.…”
Section: Epm2amentioning
confidence: 99%
See 1 more Smart Citation